An Entrepreneurial Approach to Government Employee Family Welfare in Developing Countries KPK (Pakistan) Police Employee Wellbeing Gratifying the Distinguished Services of Police Employees - Rahatullah Muhammad Khan (Communications of International Proceedings, 2020)
Developing countries like Pakistan face challenges of payment of sufficient benefits at the superannuation to their government employees. Anticipating this the employees resort to unfair practices in an endeavour to safeguard own and family’s future post retirement. This paper identifies the problem and proposes a solution whereby the government has minimal resource investment and yet their employees and families can generate revenues on continual basis through productive family concept. The model is proposed for Khyber Pukhtoon Khwa (KPK) province police department initially and can be replicated for other government departments and countries. The concept can generate a number of jobs and raise the economic conditions at micro levels thus contributing nationally.
Keywords: Police Employee Wellbeing; Family Welfare; Entrepreneurship; Productive Families